Democracy and Education: An Introduction to the Philosophy of Education - Dewey, John, 1859-1952 (Salt Lake City, UT : Project Gutenberg, 1997)
"Democracy and Education: An Introduction to the Philosophy of Education" by John Dewey is a book published in 1916. Dewey argues that education bridges the gap between immature newcomers and mature members of society. Without deliberate instruction, each generation cannot inherit the knowledge, customs, and skills necessary to sustain civilization. As societies grow more complex, this educational challenge intensifies. Though influential, Dewey's ideas were never fully adopted in American schools, and critics question his emphasis on occupations over aesthetic origins of thought. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Democracy_and_Education
Release date is 1997-03-01
Produced by David Reed and David Widger
Keywords: Education -- Social aspects; Education -- Philosophy